Evaluating the Effectiveness of the GenBI Work Program in Developing Leadership Skills in Young Leaders - Noor Diana Anindya A.R; Sutrisno Sutrisno; Sunarto Sunarto (STAI Hubbulwathan Duri, 2025)
Despite active participation in organizations, many young individuals lack strong leadership and collaborative skills. The GenBI Community (Generasi Baru Indonesia) serves as a platform to cultivate leadership qualities through structured work programs. This study evaluates the effectiveness of GenBI’s work programs in shaping leadership attributes among the younger generation. A quantitative approach was employed with data collected from 100 respondents across three case study locations: Muhammadiyah Ponorogo University Commissariat, IAIN Ponorogo, and UNIDA Gontor. A structured questionnaire was used to assess leadership indicators, including fairness, instructional ability, discipline, and responsibility. Data analysis was conducted using Welch’s ANOVA to determine the significance of the program's impact. The findings indicate that GenBI’s work programs effectively foster leadership qualities among participants. Key indicators such as fairness, the ability to give instructions, discipline, and responsibility were prominently developed. Welch’s ANOVA results (significance = 0.107) support the conclusion that leadership skills are positively influenced by participation in these programs. The study highlights the impact of GenBI’s main work programs, particularly GEBETAN (GenBI Independent Food Commodity) and Dedication to the Country, in strengthening leadership capabilities. The program employs innovative strategies that inspire and empower youth to assume leadership roles. GenBI's structured programs play a significant role in shaping leadership among young individuals. The effective strategies developed can be adapted to other organizations and communities, fostering broader leadership development across diverse environments.